2013
DOI: 10.9790/3008-0836064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different agro-waste substrates and their combinations on the yield and biological efficiency of Pleurotus sajor- caju

Abstract: Pleurotus sajor-caju Singer (Fr.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Deshmukh and Deshmukh (2016) reported that Pleurotus florida required 13 to 19 days for complete spawn run on different substrates. The days required for pinhead formation ranges from 21.40 days (wheat straw 100%) to 28.70 days in (tulsi stalk 100%) earlier reported by Dehariya and Vyas (2013) (32.00 days), Iqbal et al, (2016) reported that time duration required for pinhead formation varies between 17 to 23 days, and in combination with three different ratioˈs, ranges from 26.89 days (paddy straw + sugarcane bagasse 50:50) to 33.67 days in (wheat straw + tulsi stalk 25:75).…”
Section: Spawn Run and Pinhead Formationmentioning
confidence: 82%
“…Deshmukh and Deshmukh (2016) reported that Pleurotus florida required 13 to 19 days for complete spawn run on different substrates. The days required for pinhead formation ranges from 21.40 days (wheat straw 100%) to 28.70 days in (tulsi stalk 100%) earlier reported by Dehariya and Vyas (2013) (32.00 days), Iqbal et al, (2016) reported that time duration required for pinhead formation varies between 17 to 23 days, and in combination with three different ratioˈs, ranges from 26.89 days (paddy straw + sugarcane bagasse 50:50) to 33.67 days in (wheat straw + tulsi stalk 25:75).…”
Section: Spawn Run and Pinhead Formationmentioning
confidence: 82%
“…Rice bran showed best supplementation for mycelial growth and yield with all substrates . Dehariya and Vyas (2013) determined the effect of different agro-wastes viz. soybean straw, wheat straw, paddy straw, sugarcane bagasses, sun flower stalks, maize stalks, domestic waste, used tea leaves, fruit waste, semal flowers, news paper, bamboo leaves, sawdust and their combinations in 1:1 proportion in P. sajor-caju cultivation (yield and BE).…”
Section: Yield Biological Efficiency and Morphological Parameters Ofmentioning
confidence: 99%
“…In addition to food value, medicinal value of mushrooms for diabetics and in cancer therapy has been reported (Sivrikaya et al, 2002). Oyster mushrooms grow on different agricultural waste substrates containing lignin and cellulose like paddy straw, wheat straw, sugarcane bagasse, banana leaves, paper etc and transform lignocellulosic waste residues into protein rich food with medicinal properties (Dehariya and Vyas, 2013;Hossain, International The present investigation was carried out to know the effect of different grains such as paddy, maize, wheat, sorghum and ragi on linear mycelial growth for spawn development, yield performance and biological efficiency of Pleurotus sajorcaju. Maximum mycelial growth of P. sajorcaju was recorded in ragi grains which was on par with sorghum grains followed by wheat grains, paddy grains and maize grains.…”
Section: Introductionmentioning
confidence: 99%